Personalized Periodontal Regeneration: Integrating 3D Bioprinting with Autologous Activated Growth Factor (AGF) for Enhanced Alveolar Bone Defect Healing - Zelka Dapala; Rachmat Hidayat; Muhammad Ashraf (HM Publisher, 2025)
Background: The complete structural restoration of alveolar bone defects remains a critical challenge in reconstructive periodontology. Conventional grafting methods often fail to replicate the complex microarchitecture of periodontal tissues. This study integrated three-dimensional bioprinting technology with Autologous Activated Growth Factor to construct personalized scaffolds for treating severe infrabony periodontal defects. Methods: A randomized controlled clinical study was conducted at a private hospital in Palembang, South Sumatera, involving patients with Stage III periodontitis exhibiting vertical alveolar bone defects. Cone-beam computed tomography data guided the precise three-dimensional bioprinting of polycaprolactone and beta-tricalcium phosphate scaffolds. These constructs were functionalized operatively with Autologous Activated Growth Factor prepared from peripheral blood. The control group received conventional deproteinized bovine bone mineral with a collagen membrane. Clinical attachment level, probing depth, and radiographic bone fill were evaluated over six months. Results: The three-dimensional bioprinted scaffolds functionalized with Autologous Activated Growth Factor demonstrated superior clinical outcomes. At six months, the experimental group showed a mean probing depth reduction of 4.82 mm and a clinical attachment level gain of 4.15 mm. Radiographic analysis revealed a mean bone fill of 82.4% in the experimental group compared to 64.1% in the control. Inflammatory biomarkers were significantly modulated, indicating a highly favorable regenerative microenvironment. Conclusion: The synergistic integration of personalized three-dimensional bioprinted scaffolds with the potent osteoinductive and angiogenic properties of Autologous Activated Growth Factor significantly enhanced alveolar bone defect healing, providing a highly predictable alternative for complex periodontal regeneration.